Data mining and safety analysis of BTK inhibitors: A pharmacovigilance investigation based on the FAERS database - Wan, Qing; Li, Qiang; Lai, Xin; Xu, Tiantian; Hu, Jinfang; Peng, Hongwei (Frontiers in Pharmacology, 2022)
OBJECTIVE The introduction of bruton’s tyrosine kinase (BTK) inhibitors was a milestone in B-cell malignancies in recent years due to its desired efficacy in chronic lymphocytic leukemia(CLL) and small cell lymphocytic lymphoma(SLL) .However, the safety issue hindered its application in clinical practice. The current study was aimed to explore the safety warning signals of BTK inhibitors in real-world setting through the FDA Adverse Event Reporting System (FAERS), and provide reference for clinical rational drug use. METHODS Due to the short marketing time(zanbrutinib and orelabrutinib), we only analyze ibrutinib and acalabrutinib in this research. All the data were obtained from FAERS database from January 2004 to December 2021. Disproportionality analysis and bayesian analysis were utilized to detect and analysis the adverse events (AEs) signals of BTK inhibitors. RESULTS A total of 43429 reports with ibrutinib were extracted and 1527 AEs were identified while 1742 reports of acalabrutinib were extracted and 220 AEs were identified by disproportionality analysis and bayesian analysis. Among those AEs, males were more prone to develop AEs(58.2% for males vs 35.6% for females in ibrutinib, and 55.9% vs 31.9% in acalabrutinib), ,and more than 30% patients suffered from AEs were over 65 years. Subsequently, we investigated the top 20 preferred terms (PT) of signal strength of ibrutinib and acalabrutinib, our results identified 25(13 vs.12) novel risk signals. Among the top 20 PT related to death reports, infectious, pneumonia, pleural effusion, fall, asthenia, diarrhoea and fatigue were both ranked high in these two BTK inhibitors. Besides, cardiac disorders was also an important death cause of ibrutinib. CONCLUSION Ibrutinib was more prone to develop AEs in patients when compared with acalabrutinib. Importantly, infections related adverse reactions, such as pneumonia, pleural effusion were the most common risk signal that related to high mortality in the both two BTK inhibitors, especially in elderly patients. Besides, cardiovascular related adverse reactions such as atrial fibrillation and cardiac failure were fatal AEs of ibrutinib. Our results would provide rationale consideration for physicians to choose the suitable BTK inhibitors for different patients and provide appropriate monitor so as to attain a safer therapy and longer survival.